Continuity of use of food delivery apps: An integrated approach to the health belief model and the technology readiness and acceptance model - Graça Miranda Silva; Álvaro Lopes Dias; Maria Sim\~ao Rodrigues (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The pandemic forced both organizations and consumers to make many adjustments to their daily lives. However, due the technological advances that have been seen in recent years, some tools have become much more widely used. Among them are the food delivery applications (FDAs) that experienced an exponential growth during the pandemic. This study proposes an integrated model based on the health belief model and the technology readiness and acceptance model to better understand the determinants of users' continuance intention to use FDAs. Empirical data collected from 288 Portuguese users of FDAs during the pandemic was analyzed using partial least squares structural equation modeling. The results show that both the perceived susceptibility to and severity of COVID-19 infection positively influenced the perceived usefulness of food delivery applications. Technology readiness is also a predictor of perceived usefulness. Both self-efficacy and technology readiness predict users' perceived ease of use. Users' continuance intention to use food delivery applications is directly influenced by perceived usefulness and ease of use and indirectly by self-efficacy, technology readiness, perceived severity, and perceived susceptibility.
Keywords: 650; continuance intention; COVID-19 pandemic; food delivery app; health belief model; technology acceptance model; technology readiness